The Berkeley Library and the veil of order: Paul Koralek in conversation with John Tuomey - Sheaf, Greg (The Library of Trinity College Dublin, 2017)
A transcript of a public conversation between architects Paul Koralek and John Tuomey, 17th November 2005, together with images taken primarily in 1967 and 1976. Produced to mark the first 50 years of the Berkeley Library, as part of a series of celebrations entitled Berkeley50.
Keywords: Manuscript, Book and Print Cultures